PENGEMBANGAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN MEMBACA SISWA PADA PELAJARAN BAHASA INDONESIA DI KELAS II SD NEGERI 308/VI RANTAU SULI - Moh Rosyid Mahmudi; Dwitri; Antik Estika Hader (STKIP Subang, 2023)
Education is process of changing the attitudes and behavior of a person group in effort to mature humans. The problem this study is low student learning outcomes due to lack of media. The aim of this research is to produce valid, practical and effective Pop-up Book media. This research uses the type of research and development (research and development). ADDIE development model has five stages, namely: Analyze, Design, Development, Implementation, Evaluation. Types of data taken from the development Pop-up book media are qualitative and quantitative data. The instrument used this study, validation of the Pop-up Book media, the practicality instrument Pop-up Book media, the effectiveness instrument the Pop-up book media. data collection techniques used are interviews, observations, and questionnaires (questionnaire). Analysis of data in research using analysis of validity, practicality and effectiveness. The results this study are validation, practicality and effectiveness, so the following results can be obtained: The validity of the pop-up book learning media assessed by the validator, totaling 3 people, obtained a percentage of 94.7% in the very valid category, the pop-up book learning media is feasible for used and in accordance with the provisions of SDN 308/VI Rantau Suli II. Practicality is assessed from the teacher response questionnaire and student response questionnaire. The teacher response questionnaire was 96% in the very practical category, the student response questionnaire was 99.71% in the very practical category, so based this analysis it was concluded that pop-up book media was very practical. Furthermore, the effectiveness assessed from the results of the Reading Ability test obtained a percentage of 84.21% in the very effective category.